The Magnificat musicians as biblical interpreters - Terrien, Samuel L. 1911-; Gebert, Bruce (New York, NY Paulist, 1995)
Includes bibliographical references and index.
Keywords: Magnificat -- criticism, interpretation, etc; Magnificat (music) -- history and criticism